Elevated Serum Uric Acid Predicts Angiographic Impaired Reperfusion and 1-Year Mortality in ST-Segment Elevation Myocardial Infarction Patients Undergoing Percutaneous Coronary Intervention. (1st August 2011) - Basar, Nurcan; Sen, Nihat; Ozcan, Firat; Erden, Gonul; Kanat, Selcuk; Sokmen, Erdogan; Isleyen, Ahmet; Yuzgecer, Huseyin; Ozlu, Mehmet Fatih; Yildirimkaya, Metin; Maden, Orhan; Covic, Adrian; et al.
Abstract : Background: Serum uric acid (SUA) is associated with microvascular disease that could alter coronary blood flow and prognosis. We evaluated the effects of admission SUA levels on coronary blood flow and prognosis in 185 consecutive patients with ST-segment elevation myocardial infarction (STEMI) who underwent acute primary percutaneous coronary intervention (PCI). Methods: Patients undergoing PCI for an acute STEMI were stratified into elevated SUA (>6.5 mg/dL) and normal SUA group (≤6.5 mg/dL). Primary end points were post-PCI myocardial blood flow and in-hospital and 1-year mortality. Results: Serum uric acid level was high in 45 patients (24%) on admission. Subjects with elevated SUA had a higher prevalence of hypertension, previous myocardial infarction, multivessel disease, and Killip functional class III or higher. Corrected thrombolysis in myocardial infarction (TIMI) frame count was longer, and mean TIMI myocardial perfusion grade was higher in patients with elevated uric acid compared with controls. Patients with elevated SUA levels had higher in-hospital (6.6% vs 2.8%, P < 0.01) and 1-year mortality (11.1% vs 5.7%, P < 0.01). Major adverse cardiac events were higher in patients with elevated SUA levels both in-hospital (11.1% vs 5.7%, P < 0.01) and at 1 year (17.7% vs 10%, P < 0.05). An elevated admission SUA level also independently predicted both 1-year mortality (odds ratio, 1.41; 95% confidence interval, 1.24-2.69) and abnormal myocardial perfusion detected by TIMI myocardial perfusion grade in STEMI patients undergoing primary PCI (odds ratio, 2.14; 95% confidence interval, 1.17-4.19, respectively). Conclusions: Elevated SUA level on admission independently predicts impaired myocardial flow and poor prognosis in STEMI patients undergoing primary PCI.